Chalcogenoether complexes of tantalum(V) sulfide trichloride – Synthesis, properties and structures. (1st September 2019) - Bannister, Robert D.; Levason, Willian; Reid, Gillian; Robinson, Fred
Graphical abstract: A series of very unusual Ta(V) sulfide trichloride complexes with soft, neutral dithioether and diselenoether co-ligands is reported and fully characterised. Abstract: The complexes [TaSCl3 (L-L)] (L-L = MeSCH2 CH2 SMe, i PrSCH2 CH2 S i Pr, PhSCH2 CH2 SPh, n BuSCH2 CH2 CH2 S n Bu, MeSCH2 CH2 CH2 SMe, MeSeCH2 CH2 SeMe, n BuSeCH2 CH2 CH2 Se n Bu) have been synthesised and isolated in good yield as powdered solids by the reaction of TaCl5 with the appropriate chalcogenoether in a 1:1 molar ratio in anhydrous CH2 Cl2 solution at room temperature, followed by the addition of a CH2 Cl2 solution containing one mol. equiv. of S(SiMe3 )2 . The isolated complexes were characterised by IR, 1 H and 77 Se 1 H NMR spectroscopy, as appropriate, and elemental analysis. Single crystal X-ray structure analyses for [TaSCl3 (MeSCH2 CH2 SMe)], [TaSCl3 (MeSeCH2 CH2 SeMe)], [TaSCl3 ( i PrSCH2 CH2 S i Pr)] and [TaSCl3 ( n BuSCH2 CH2 CH2 S n Bu)] have been obtained. The data are compared with the previously described Nb(V) analogues. In contrast to the corresponding [NbSCl3 (E n Bu2 )] (E = S, Se), attempts to isolate [TaSCl3 (E n Bu2 )] were unsuccessful. Low pressure chemical vapour deposition (LPCVD) experiments using [TaSCl3 ( n BuSCH2 CH2 CH2 S n Bu)] did not lead to any deposition, whilst similar experiments using [TaSCl3 ( n BuSeCH2 CH2 CH2 Se n Bu)] produced films containing only elemental Se, with no evidence for any deposition of tantalum sulfide or selenide films.